2020
DOI: 10.1016/j.bja.2019.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with persistent pain after childbirth: a narrative review

Abstract: A systematic literature search was performed to identify studies that reported risk factors for persistent pain after childbirth. Many studies have sought to identify risk factors for post-delivery pain in different populations, using different methodologies and different outcome variables. Studies of several different but interrelated post-partum pain syndromes have been conducted. Factors strongly and specifically associated with persistent incisional scar pain after Caesarean delivery include a coexisting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 124 publications
1
37
0
7
Order By: Relevance
“…Women have more chronic pain (21.7% vs. 19%, P < 0.05) and more high-impact chronic pain (8.5% vs. 6.3%, P < .05) than men, even affecting 9-15% of 18-44 year olds [ 10 ]. Previous studies have shown an association between higher pain scores after delivery with a higher incidence of postpartum depression and development of chronic pain [ 3 , 6 , 11 ••, 12 •]. Higher pain postdelivery has been associated with lower rates of breastfeeding as well as a higher incidence of postpartum depression and chronic pain [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women have more chronic pain (21.7% vs. 19%, P < 0.05) and more high-impact chronic pain (8.5% vs. 6.3%, P < .05) than men, even affecting 9-15% of 18-44 year olds [ 10 ]. Previous studies have shown an association between higher pain scores after delivery with a higher incidence of postpartum depression and development of chronic pain [ 3 , 6 , 11 ••, 12 •]. Higher pain postdelivery has been associated with lower rates of breastfeeding as well as a higher incidence of postpartum depression and chronic pain [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine, an NMDA receptor antagonist, has analgesia effect and has been used for prevention of acute and chronic pain, hyperalgesia, and central sensitization and may prevent acute opioid tolerance [ 12 •, 42 ]. S-Ketamine (dose of 0.5 mg/kg IM followed by 2 mcg/kg/min IV infusion for 12 h) significantly decreased morphine consumption after CD starting at 8 h and by 31% over 24 h, increased time to first morphine use, and trended to reduced hyperalgesia at T10 [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain intensity has been observed to be higher after vaginal delivery than caesarean delivery, severely affecting mood and quality of life [ 56 58 ]. Although we did not query participants about vaginal tearing in this survey, it may be that the participants with vaginal delivery also had significant perineal trauma, which has been linked with persistent postpartum pain [ 59 ]. The findings of this study highlight that when evaluating a postpartum runner with running-related pain, questions about delivery should be routinely asked due to the potential contribution to pain intensity and potential recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Concerningly, long-term psychological outcomes may be associated with having general anesthesia for cesarean delivery. Several studies show an association between general anesthesia for cesarean delivery and persistent pain beyond the expected healing time [ 70 ]. Although quite controversial, a recent retrospective study using the New York State inpatient database suggested that general anesthesia for cesarean delivery is associated with severe postpartum depression requiring hospitalization as well as self-harm and suicidal ideation [ 71 ].…”
Section: Anesthesia-related Complications and Concernsmentioning
confidence: 99%